Personal branding : a case study on how individuals can develop themselves as their own personal brand - Rahmani, Sepide; Särhammar, Anna (2010)
Today’s competitive society has made it hard to distinguish ourselves from others and to reach our professional goals. The purpose of this study is to provide a better understanding of how individuals can develop as their own personal brand. Two research questions focus on The study has a qualitative approach and via two research questions focusing on the objectives/benefits of personal branding, as well as the strategies used in developing yourself as a personal brand. A qualitative, case study methods is used, with interviews being the main data collection tool. Interviews were conducted with students currently attending Luleå University of Technology in Sweden. The findings indicate that the main objective to actually develop a personal brand is more or less to gain employment, where a personal brand will help you stand out among your competitors. As there have been quite limited research within this area, it was not surprising to discover that personal branding is not yet practiced to the extent that it could be. However, the interest among people for this phenomenon is both needed and strong. Validerat; 20101217 (root)